2013
DOI: 10.3389/fnhum.2013.00035
|View full text |Cite
|
Sign up to set email alerts
|

How to engage the right brain hemisphere in aphasics without even singing: evidence for two paths of speech recovery

Abstract: There is an ongoing debate as to whether singing helps left-hemispheric stroke patients recover from non-fluent aphasia through stimulation of the right hemisphere. According to recent work, it may not be singing itself that aids speech production in non-fluent aphasic patients, but rhythm and lyric type. However, the long-term effects of melody and rhythm on speech recovery are largely unknown. In the current experiment, we tested 15 patients with chronic non-fluent aphasia who underwent either singing therap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
59
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(64 citation statements)
references
References 59 publications
(76 reference statements)
2
59
0
Order By: Relevance
“…This would require partner questionnaires, which are not very reliable. Anecdotic reports from partners suggest that patients did benefit from the improvement on trained utterances in daily life; this is in line with the results of Stahl et al 20 Remarkably, the present study also showed that a small difference in the timing of MIT had considerable consequences for its effect. A delay of merely 6 weeks was related to less improvement.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This would require partner questionnaires, which are not very reliable. Anecdotic reports from partners suggest that patients did benefit from the improvement on trained utterances in daily life; this is in line with the results of Stahl et al 20 Remarkably, the present study also showed that a small difference in the timing of MIT had considerable consequences for its effect. A delay of merely 6 weeks was related to less improvement.…”
Section: Discussionsupporting
confidence: 92%
“…Several therapeutic elements of MIT may be responsible for its effects on language production: melody, rhythm, hand tapping, or reduction of speed in singing versus speaking. 20,21,38,39 A recent study comparing the effect of melody and rhythm on language production in nonfluent aphasia showed that melody had no additional effect over rhythm. 20 In the present study, it was impossible to unravel the impact of the MIT components, since we used the original MIT technique.…”
Section: Discussionmentioning
confidence: 99%
“…They compared melodic therapy with rhythmic therapy and spoken therapy in a cross-over design in three individuals with chronic Broca's aphasia. Their results showed, in contrast to Stahl et al (2013), that only the melodic therapy, which consisted of both pitch and rhythm, significantly improved speech production. The above-mentioned controlled studies have demonstrated the importance of using musical elements in the efficacy of MIT, including various modifications on MIT, without leading to an understanding of which therapeutic elements, melody or rhythm, contribute to its success.…”
mentioning
confidence: 86%
“…In individuals with AoS, these aspects can be disturbed in speech production (Ziegler, 2008). As mentioned earlier, MIT uses two musical elements: rhythm and melody of which both underlying mechanisms are still unclear (Stahl et al, 2013;Zumbansen et al, 2014b). However, MIT structures are restricted to two notes and two durations.…”
mentioning
confidence: 99%
See 1 more Smart Citation